Cyclical Dynamics of Beef Market Price in Yogyakarta Province: A Cobweb Model Approach - Agung Triatmojo; Mujtahidah Anggriani Ummul Muzayyanah (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Fluctuations in agricultural food prices, particularly for animal proteins like beef, have profound implications for Yogyakarta beef market, imposing significant budgetary constraints on consumers, disrupting market equilibrium, and creating uncertainty for farmers. Understanding the drivers of cyclical price dynamics is critical for effective policy intervention and market regulation to mitigate these challenges. Therefore, this study specifically investigates determinants of cyclical beef price behavior in Yogyakarta, Indonesia. Utilizing time series data from 1989 to 2018, a two-stage least squares (2SLS) approach in natural logarithm form is employed to identify the factors influencing beef demand and supply. The 2SLS method was chosen to address potential simultaneity bias arising from the interdependence of beef price and quantity, ensuring more accurate estimation of the relationships between these variables. Log-log regression model is then employed to determine market equilibrium based on Cobweb Model. Although the Cobweb Model simplifies price expectations and market complexities, its focus on cyclical dynamics and data accessibility makes it suitable for analysing cyclical price patterns in the beef market. The results revealed that beef demand is significantly influenced by price (0.203%) and per capita income (0.485%) , while supply is driven by price (0.075%), cattle population growth (0.403%), and slaughter numbers (0.425%). The findings indicated a convergent fluctuation pattern, with demand elasticity exceeding supply elasticity (0.471 > 0.343). This research contributed to understanding of price dynamics and market equilibrium in the context of local beef market, demonstrating the applicability of the Cobweb Model in explaining cyclical adjustments in price and quantity.